Formulation and Evaluation of Solid Dispersion Griseofulvin Tablets - Karima, Nurul (Pustaka Media Publishing, 2024)
Griseofulvin is one of the systemic treatments for the treatment of dermatophytes found on the skin, scalp and nails. Griseofulvin is a BCS class II group that has low solubility and high permeability. Increasing solubility is one of them by using a solid dispersion system. In this study, the solid dispersion obtained was formulated in tablet form. The purpose of this study was to increase the solubility of griseofulvin. The method used was experimental, solid dispersion using PEG 6000 as a carrier, with XRD, SEM, and FTIR test parameters. Furthermore, the solid dispersion obtained was formulated in tablet form and tablet characteristics were tested, namely: preformulation test, hardness test, friability test, disintegration time test, and dissolution test. The results of the test of the characteristics of solid dispersion griseofulvin tablets met the requirements. The results of the dissolution test showed that griseofulvin tablets showed a higher cumulative percentage compared to conventional tablets, namely at 90 minutes the cumulative percentage was 88.81%.